Opportunity to discuss ethical issues during clinical learning experience. (September 2019) - Palese, Alvisa; Gonella, Silvia; Destrebecq, Anne; Mansutti, Irene; Terzoni, Stefano; Morsanutto, Michela; Altini, Pietro; Bevilacqua, Anita; Brugnolli, Anna; Canzan, Federica; Ponte, Adriana Dal; De Biasio, Laura; et al.
Background: Undergraduate nursing students have been documented to experience ethical distress during their clinical training and felt poorly supported in discussing the ethical issues they encountered. Research aims: This study was aimed at exploring nursing students' perceived opportunity to discuss ethical issues that emerged during their clinical learning experience and associated factors. Research design: An Italian national cross-sectional study design was performed in 2015–2016. Participants were invited to answer a questionnaire composed of four sections regarding: (1) socio-demographic data, (2) previous clinical learning experiences, (3) current clinical learning experience quality and outcomes, and (4) the opportunity to discuss ethical issues with nurses in the last clinical learning experience (from 0 – 'never' to 3 – 'very much'). Participants and research context: Participants were 9607 undergraduate nursing students who were attending 95 different three-year Italian baccalaureate nursing programmes, located at 27 universities in 15 Italian regions. Ethical considerations: This study was conducted in accordance with the Human Subject Research Ethics Committee guidelines after the research protocol was approved by an ethics committee. Findings: Overall, 4707 (49%) perceived to have discussed ethical issues 'much' or 'very much'; among the remaining, 3683 (38.3%) and 1217 (12.7%) students reported the perception of having discussed, respectively, 'enough' or 'never' ethical issues emerged in the clinical practice. At the multivariate logistic regression analysis explaining 38.1% of the overall variance, the factors promoting ethical discussion were mainly set at the clinical learning environment levels (i.e. increased learning opportunities, self-directed learning, safety and nursing care quality, quality of the tutorial strategies, competences learned and supervision by a clinical nurse). In contrast, being male was associated with a perception of less opportunity to discuss ethical issues. Conclusion: Nursing faculties should assess the clinical environment prerequisites of the settings as a context of student experience before deciding on their accreditation. Moreover, the nursing faculty and nurse managers should also enhance competence with regard to discussing ethical issues with students among clinical nurses by identifying factors that hinder this learning opportunity in daily practice.